2012
DOI: 10.1021/jp304672t
|View full text |Cite
|
Sign up to set email alerts
|

Directed Self-Assembly of Colloidal Model Systems on Charge-Selective Surfaces in External Electric Fields: Theory and Numerical Analysis

Abstract: Membrane electrophoretic deposition has a long-established reputation in delivering high quality nanoparticle compact and coating solutions in the field of high performance nanoparticle architectures made from aqueous nanoparticle suspensions. Although for a long time, it has been common practice in nanoparticle science and particle-based nanotechnology to use membrane electrophoretic shaping of nanoparticles, little is known about long-range electrohydrodynamic manipulation of the engineered assembly of collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…S8) allow characterization of the granular microcrystalline structure of the formed ZnO film. Although oriented attachment [35][36][37] seems to occur in areas close to the surface, the overall film consists of randomly oriented ZnO crystallites.…”
Section: Semiconducting Properties and Field Effect Transistor Devicementioning
confidence: 99%
“…S8) allow characterization of the granular microcrystalline structure of the formed ZnO film. Although oriented attachment [35][36][37] seems to occur in areas close to the surface, the overall film consists of randomly oriented ZnO crystallites.…”
Section: Semiconducting Properties and Field Effect Transistor Devicementioning
confidence: 99%
“…It has to be noted that this model is based on a charge discontinuity in the area of the membrane pore without the influence of any external potentials. A detailed description of the FEM approach is given anywhere else [6,7].…”
Section: Electrohydrodynamic Model and Fem Representationmentioning
confidence: 99%
“…10 However, the deposition mechanism is not fully understood, although investigating NP dynamics under an electric field is crucial to uncovering the origin of NP movements in a solution and enhancing the deposition efficiency. 19 Typically, liquid cell transmission electron microscopy is a widely used technique for observing colloidal NP processes such as growth, 20 chemical transformation, 21 and diffusion. 22 However, observing NP dynamics using a liquid cell transmission electron microscope under an electric field is less favored because the NPs travel macroscopically during EPD from micrometers to centimeters.…”
mentioning
confidence: 99%
“…Kang et al demonstrated that the type of nonpolar solvent determines the morphological characteristics of EPD products . However, the deposition mechanism is not fully understood, although investigating NP dynamics under an electric field is crucial to uncovering the origin of NP movements in a solution and enhancing the deposition efficiency …”
mentioning
confidence: 99%